2001
DOI: 10.1097/00124509-200103000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Nitroprusside and ECS-Induced Retrograde Amnesia

Abstract: Previous research found that the administration of verapamil and felodipine immediately before electroconvulsive shocks (ECS) attenuated ECS-induced retrograde amnesia. This study examined whether sodium nitroprusside, an antihypertensive drug that does not affect calcium channels, has a similar action. Adult male Sprague-Dawley rats received nitroprusside (0.5 mg/kg ip) or saline 3 minutes before each of three once-daily true or sham ECS. Retention of pre-ECS learning was studied 1 day after ECS using a passi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The hyperdynamic state induced by sympathetic activation can be prevented by ganglion-blockers [46], betablockers [47][48][49][50][51][52][53][54][55][56][57][58][59]67,77], alpha-1 and alpha2-agonists [60][61][62][63][64][65][66], Ca2+-channel antagonists [68][69][70], nitrates [71][72][73][74][75][76] or local anesthetics [78]. Rapid, short-acting opioid [79][80][81] analgesics also possess sympatholytic effects and have recently been investigated as adjuvants during ECT.…”
Section: Drugs Used For Hemodynamic Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperdynamic state induced by sympathetic activation can be prevented by ganglion-blockers [46], betablockers [47][48][49][50][51][52][53][54][55][56][57][58][59]67,77], alpha-1 and alpha2-agonists [60][61][62][63][64][65][66], Ca2+-channel antagonists [68][69][70], nitrates [71][72][73][74][75][76] or local anesthetics [78]. Rapid, short-acting opioid [79][80][81] analgesics also possess sympatholytic effects and have recently been investigated as adjuvants during ECT.…”
Section: Drugs Used For Hemodynamic Stabilizationmentioning
confidence: 99%
“…In addition, Sudha et al [76] demonstrated the efficacy of 0.5 mg/kg of sodium nitroprusside administered intraperitoneally in increasing seizure duration in rats.…”
Section: Nitratesmentioning
confidence: 99%
“…Reportedly, NO was not involved in retrieval formation in olfactory memory task in the adult sheep (Kendrick et al 1997), in the newborn rat (Samana and Boehm 1999), and in a passive avoidance test in the mouse (Telegdy and Kokavszky 1997). In contrast, involvement of NO in the retrieval of information was reported in inhibitory memory tasks performed in the newborn rat (Myslivecek et al 1996) and in the adult rat (Sudha et al 2001).…”
Section: Discussionmentioning
confidence: 88%
“…[181184] Curiously, two of the blood pressure surge studies themselves suggested neurotransmitter mechanisms. [177178]…”
Section: Mechanisms Underlying Ect-induced Amnestic Deficitsmentioning
confidence: 99%
“…In order to further investigate our hypothesis, we studied the effects of a different antihypertensive agent: sodium nitroprusside[177] and we separately asked whether increasing blood pressure, using phenylephrine, worsens amnestic deficits with ECT. [178]…”
Section: Mechanisms Underlying Ect-induced Amnestic Deficitsmentioning
confidence: 99%